Daprodustat: A potential game-changer in renal anemia therapy-A perspective - Muhammad Usman Haider; Muhammad Furqan; Qasim Mehmood (Frontiers Media S.A., 2023)
The United States FDA has approved daprodustat (DPD) as the first oral treatment option for anemia due to chronic kidney disease (CKD) in dialysis patients. Clinical trials have demonstrated DPD's efficacy and safety, showing non-inferiority to darbepoetin and suggesting reduced IV iron usage. DPD also holds potential for treating chronic kidney disease anemia in non-dialysis patients and may have benefits for patients with coexisting renal anemia and heart failure, pending further research and trials.